The Analysis of Murabahah bil Wakalah Agreements Implementation Consistency toward Sharia Financial Institutions in Indonesia - Moh. Wahyu Al Waris; Nuzulia Kumala Sari (Rechtenstudent, 2023)
Murabahah bil wakalah is buying and selling using the wakalah system. In this buying and selling system, the seller represents his purchase to the customer, thus the first contract is a wakalah contract after the wakalah contract ends which is marked by the delivery of goods from the customer to the Sharia Financial Institution (LKS), then the institution provides a murabahah contract. The practice of murabahah bil wakalah financing in several LKS, namely at PNM Mekaar Syariah West Aceh Branch, Bank BRI Syariah KCP Majayala, KSPPS Istiqamah Padang Panjang, Bank DKI Head Office, and Bank Mualamalat Indonesia Malang Branch . This research is deemed necessary to formulate how the Murabahah bil wakalah agreement should be applied in financing so as not to violate the rules of muamalah fiqh. Meanwhile, this research method uses a normative juridical research type with a statutory approach and a conceptual approach. The results of this research show that the murabahah financing practices in several LKS above do not meet the pillars and requirements of murabahah as stipulated in Islamic law. So it is doubtful that the sharia value of the contract carried out is formally something that is not fulfilled.